Cr(VI) removal from aqueous solution by iron (III) hydroxide-loaded sugar beet pulp - Altundogan, HS (Elsevier Sci Ltd, 2005)
In this study. a composite adsorbent was prepared from sugar beet pulp by loading with iron (III) hydroxide and its Cr(VI) removal properties from aqueous solutions were investigated. For this purpose, sugar beet pulp was subjected to the treatments of saponification, ferric chloride impregnation. hydrolysing and heating. Thus, the individual effects of these treatments on the Cr(VI) removal properties of pulp were determined. Results of standardised adsorption experiments showed that the most suitable adsorbent is the hydrolysing product of ferric chloride impregnated-saponified sugar beet pulp (PSFH). Maximum total chromium-removal efficiency of PSFH was 83.1 % at the final pH of 4.4 for the conditions of 10 mg l(-1) Cr(VI) concentration, 120 min contact time and 25 degreesC. Also, it was found that the reduction of Cr(VI) occurred during the sorption process is an important issue. Data obtained from the Cr(VI) adsorption study carried out by PSFH were well fit to the Lagergren and Langmuir equations. Also, thermodynamic calculations showed that the process is exothermic and spontaneous. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: sugar beet pulp; hexavalent chromium; iron (III) hydroxide; adsorption; reduction